Education as seen by young voices - Vallejos Lizárraga, Rosa Amelia (2018)
Education is a fundamental right recognized in the Constitution and in national and international regulations. However, this paper mainly considers elementary and high schools, as it is one of the spaces where children and adolescents grow throughout fourteen years of their lives.From adolescent voices’ perspective, the foundation of education is based on the results of the Young Voice Peru Survey (adolescent voices) applied by Save the Children Peru and the Young Voice Peru 2017 Report. The starting point is to recognize the importance of raising awareness on the Convention on the Rights of the Child and, in that sense, their rights. The survey shows that almost half of the adolescents has never heard about the Convention and, on top of that, there is confusion about its content. In this review of the subject, it is important not to lose sight of the fact that adolescents attach value to education on the basis of their relationship with their school. Since education is a right, it should not be violated through practices that do not take into account students’ opinions, especially if they do not feel safe in this environment or where part of their fundamental concerns is to comply with school assignments thatthey sometimes do not understand or have no help at home.